Teaching with love & logic : taking control of the classroom - Fay, Jim.; Funk, David, 1946- (Golden, CO : Love and Logic Press, 1995)
A guide for educators on classroom management that discusses positive disciplinary techniques to increase the level of student responsibility and their abilities to think for themselves.
Includes bibliographical references (p. 373-390) and index.
Adult
Keywords: Classroom management -- United States; School discipline -- United States; Classroom management; School discipline